Development of a mathematical model of solar converter efficiency - Столярчук, Петро Гаврилович; Микийчук, Микола Миколайович; Яцук, Василь Олександрович; Міхалєва, Марина Станіславівна; Шпак, Оксана Іванівна; Олеськів, Тарас Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
A mathematical model of the solar collector efficiency is proposed to assess the effectiveness of their operation and quickly monitor their application. The mathematical model is represented by an interval, which is divided into four segments, depending on the purpose of using solar cells. These segments determine inefficient, moderately efficient, efficient and highly efficient operation of the solar collectors. The determination of the solar cells’ efficiency allows making decisions about their future use. The proposals are worked out to improve the solar collector test methods by increasing the accuracy of measuring the main components. The measures are proposed to reduce the temperature difference measurement errors by several times for improving the accuracy of calculating the efficiency coefficient of the solar collectors approximately twice.